The “straight man” and the phallus: the sustenance of power in the discoursive order - Silva, Valter Souza da; Oliveira, Rosimar Regina Rodrigues de (Entrepalavras, 2025)
The heterosexual discourse in phallocentric self-affirmations, which is delineated in this article, contributes to the discursive development of masculinity. The penis is a recurrent element in statements by certain social groups as an item that attests to power. This text corpus is a speech given on September 7, 2022, by former President Bolsonaro. The key “never limp” passage is condensed to explain the connection between the founding discourse and the identification process of the “straight man”, which is permitted to circulate on a regular basis. Considering the inherent patterns of ideological formations which have materiality in discursive formations that are expressed explicitly in social actions that are largely replicated. The theoretical contribution is the Franco-Brazilian Discourse Analysis research area, from the writings of Michel Pêcheux and translated into Brazilian by Eni Orlandi. Throughout corpus analysis, it becomes clear that the speech is a recollection of other remarks, in this case, ones that are discriminatory, sexist, and segregationist. In addition, there has been a reinvestment in ideological norms like patriarchy, sexism, and conservatism.